12q21 deletion syndrome: Narrowing the critical region down to 1.6 Mb including SYT1 and PPP1R12A. Issue 9 (6th July 2020) - Niclass, Tanguy; Le Guyader, Gwenael; Beneteau, Claire; Joubert, Madeleine; Pizzuti, Antonio; Giuffrida, Maria Grazia; Bernardini, Laura; Gilbert‐Dussardier, Brigitte; Bilan, Frederic; Egloff, Matthieu
Abstract: Deletions in the 12q21 region are rare and non‐recurrent CNVs. To date, only 11 patients with deletions in this region have been reported in the literature. These patients most often presented with syndromic intellectual deficiency, ventriculomegaly or hydrocephalus, ectodermal abnormalities, growth retardation and renal and cardiac malformations, suggesting a recognizable microdeletion syndrome. We report three new patients with overlapping deletions of the 12q21 region, including the smallest deletion reported to date and the first case characterized by array CGH during pregnancy. We describe specific clinical findings and shared facial features as developmental delay, ectodermal abnormalities, ventriculomegaly or hydrocephalus, axial hypotonia or spastic diplegia, growth retardation, heart defect, hydronephrosis, ureteral reflux or horseshoe kidney, large thorax or pectus excavatum, syndactyly of 2–3 toes, pterygium coli or excess nuchal skin, large anterior fontanel, low set ears, prominent forehead, short‐upturned nose with nostril hypoplasia, microretrognathia and hypertelorism. These new patients and a comprehensive review of the literature allow us to define a minimum critical region spanning 1.6 Mb in 12q21. By screening the critical region using prediction tools, we identified two candidate genes: SYT1 and PPP1R12A .